Comparative Analysis of Reference Desk Services: the Current Trends in a Digital Age - Jasni, Nurul Diana (2017)
Recent studies show that library trends in reference usage patterns are shifting. User preference for using online resources is increasing and becoming more predominant in many Malaysian academic libraries. The decline in the number of students using the physical library has lessened the need for librarians. In order to get library resources, users do not have to be physically presents into the library building. User trends and patterns have changed and now library users favor the use of online assistance, consultation, advisory and guidance to meet their information needs. Changes in user query have impacted the way the library provides services, but traditional reference services will still remain as the core of information services. This paper aims to 1) provides a unique snapshot of a reference service in an academic library, where both online and offline reference services are taking place; 2) to described on how a reference services librarian may have the best influence on the visibility and operational of an academic library. By analyzing the trends from the usage statistics, this study can be used as a continuous improvement where reference librarians need to enhance their digital competencies in providing reference desk assistance.